CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE, KARAKTERISTIK PERUSAHAAN DAN PENGARUHNYA TERHADAP EARNINGS RESPONSE COEFFICIENT - Ega Budi Pranowo; Hiras Pasaribu (Program Magister Akuntansi Unsyiah, 2013)
This study is aimed to determine the effect of disclosure of Corporate Social Responsibility (CSR), the characteristics of the enterprises in the form of company size, and Institutional Ownership on Earnings Response Coefficient (ERC). This study sampled a total of 33 manufacturing companies according to certain criteria of population. The results show the simultaneous effect of disclosure of CSR, company size and institutional Ownership of the ERC. Partial results show that the negative effect on the disclosure of CSR ERC, company size is not very influential and have a negative relationship to the ERC, and Institutional Ownership has positive influence on Earnings Response Coefficient. Keywords: CSR, Ownership, Earnings Response Coefficient.